Caring Behavior of Caregivers During The Satisfy of Basic Needs in The Elderly - Febrina, Wiwit; Said, Farida Mohd; Rezkiki, Fitrianola; Rahmiwati, Rahmiwati; Lazdia, Wenny (REAL in Nursing Journal, 2025)
Background: Entering old age, a person experiences a process of changing body functions both physically and psychologically, which can cause the elderly to have difficulty in achieving their basic needs. The Caring behavior is a form of support that caregivers can provide to the elderly in an effort to protect, improve, maintain, or devote a sense of humanity by helping someone achieve a better aspect. This study aimed to determine the caring behavior of caregivers in satisfying basic needs for the elderly at West Sumatera Province in 2022. Methods: This study was conducted from March until July in 2022. The type of this study was quantitative by using a descriptive study. The population of this study was all the elderly as recipients of caring behavior directly from caregivers. By using total sampling, 53 people were chosen as the sample. The data was collected by using a questionnaire about the caring behavior of caregiver. Results: From the results, it was found that as many as 33 people (62.3%) of respondents stated that the caring behavior of caregivers was included in the good category. Conclusion: From the results of this study, it is expected that caregivers can improve the process of caring for the elderly in achieving more optimal basic satisfy through effective communication between caregivers and the elderly.